Effects of changes in mucosal solution Cl- or K+ concentration on cell water volume of Necturus gallbladder epithelium (The Rockefeller University Press, 1991)
An electrophysiologic technique was used to measure changes in cell water volume in response to isosmotic luminal solution ion replacement. Intracellular Cl- activity (aCl-i) was measured and net flux determined from the changes in volume and activity. Reduction of luminal solution [Cl-] from 98 to 10 mM (Cl- replaced with cyclamate) resulted in a large fall in aCl-i with no significant change in cell water volume. Elevation of luminal solution [K+] from 2.5 to 83.5 mM (K+ replaced Na+) caused a small increase in aCl-i with no change in cell water volume. Exposure of the Necturus gallbladder epithelium to agents that increase intracellular cAMP levels (forskolin and/or theophylline) induces an apical membrane electrodiffusive Cl- permeability accompanied by a fall in aCl-i and cell shrinkage. In stimulated tissues, reduction of luminal solution [Cl-] resulted in a large fall in aCl-i and rapid cell shrinkage, whereas elevation of luminal solution [K+] caused a large, rapid cell swelling with no significant change in aCl-i. The changes in cell water volume of stimulated tissues elicited by lowering luminal solution [Cl-] or by elevating luminal solution [K+] were reduced by 60 and 70%, respectively, by addition of tetraethylammonium (TEA+) to the luminal bathing solution. From these results, we conclude that: (a) In control tissues, the fall in aCl-i upon reducing luminal solution [Cl-], without concomitant cell shrinkage, indicates that the Cl- entry mechanism is electroneutral (Cl- /HCO3-) exchange. (b) Also in control tissues, the small increase in aCl-i upon elevating luminal solution [K+] is consistent with the recent demonstration of a basolateral Cl- conductance. (c) The cell shrinkage elicited by elevation of intracellular cAMP levels results from conductive loss of Cl- (and probably K+). (d) Elevation of cAMP inhibits apical membrane Cl-/HCO-3-exchange activity by 70%. (e) The cell shrinkage in response to the reduction of mucosal solution [Cl-] in stimulated tissues results from net K+ and Cl- efflux via parallel electrodiffusive pathways. (f) A major fraction of the K+ flux is via a TEA(+)-sensitive apical membrane K+ channel.